Introduction : Transnational Fascism - Rossoliński-Liebe, Grzegorz; Rudling, Per Anders (Routledge Studies in Fascism and the Far Right, 2025)
For many years, fascism in East Central and Southeastern Europe remained an overlooked aspect of the history of transnational and transatlantic fascism. This introduction provides a background on how this came to pass and why we should rethink this assumption. The introduction explains how the heterogeneity of East Central and Southeastern European fascism alters the general understanding of European and global fascism and what methodological and theoretical tools we need to study fascism in this part of Europe, from the 1920s until today. The introduction presents a definition of fascism and provides an analytical framework that the contributors use to interact and exchange ideas. We also familiarize the readers with important theoretical concepts within which the contributors were asked to conceptualize their chapters. Due to the wide time frame, the volume shows how fascism changed, evolved and adjusted to the very different political, social, and economic circumstances of the interwar period, World War II, the Cold War and the post-Soviet period. To study the exchange of ideas as well as practical and political collaboration between fascist movements and authoritarian regimes, we introduce concepts such as “fascistization,” “hybridization” and “amalgamation”.
Keywords: Fascism; Migration; Holocaust revisionism; Cold War; Anti-Communism; Central Europe; Eastern Europe